Externality versus economic and socialman (2013)
When we study our social realities we find positive and negative externalities, which are known for the government, its local authorities, its agencies, political leaders, unions, and in general, for the citizens. We live daily with externalities in our social life, maximizing benefits,reducing social, environmental, cultural costs, and other. We live with their effects in exchange of an accelerated economic growth which is enhanced by the globalization of the economy.